2008
DOI: 10.1111/j.1475-6773.2008.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Doctor–Patient Communication Affect Patient Satisfaction with Hospital Care? Results of an Analysis with a Novel Instrumental Variable

Abstract: The primary outcome was patients' ratings of their overall satisfaction with hospital care, and the primary independent variable was patients' ratings of their physicians' communication behaviors. To remove possible confounding of the association between patient ratings of physician communication and overall satisfaction by other patient-specific attributes, we created an instrumental variable (IV) in a two-stage linear regression. The IV was the mean of the communication ratings given to each physician by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 24 publications
6
105
1
1
Order By: Relevance
“…Interestingly, the interaction between pediatrician verbal receptivity and parent health literacy moderated all parent learning outcomes (i.e., communication satisfaction, affective learning, and cognitive learning). These findings are consistent with those of other researchers who have examined the impact of physicians' use of verbal receptivity behaviors (e.g., displaying empathy, letting the patient speak, and encouraging patients to ask questions) on positive patient outcomes (Clever et al, 2008). Wanzer and colleagues (2004) found that physician, nurse, and staff displays of empathy, listening, and other positive verbal behaviors were significant predictors of parents' satisfaction with health care in a large children's hospital.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the interaction between pediatrician verbal receptivity and parent health literacy moderated all parent learning outcomes (i.e., communication satisfaction, affective learning, and cognitive learning). These findings are consistent with those of other researchers who have examined the impact of physicians' use of verbal receptivity behaviors (e.g., displaying empathy, letting the patient speak, and encouraging patients to ask questions) on positive patient outcomes (Clever et al, 2008). Wanzer and colleagues (2004) found that physician, nurse, and staff displays of empathy, listening, and other positive verbal behaviors were significant predictors of parents' satisfaction with health care in a large children's hospital.…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted by Burgoon et al (1987), the verbal receptivity of physicians' was found to be the most important factor predicting patient affective, cognitive, and behavioral satisfaction with their healthcare. Physician communication behaviors such as asking patients for their opinions, letting patients talk without interruption, displaying empathy, and encouraging patients to ask questions all have a substantial and positive impact on patients' perceptions of care quality (Clever, Jin, Levinson, & Meltzer, 2008;Wanzer et al, 2004).…”
Section: Verbal Receptivitymentioning
confidence: 99%
“…Among them, the patient---doctor relationship, for example, has been considered essential for patient satisfaction. 10,11 Thus, when problems or difficulties arise in aspects such as communication with the healthcare staff, information received during the healthcare process, coordination, the participation of the family in assistential issues and in decision-making, the levels of user satisfaction are clearly lower. 11---15 With regard to the second and third groups of variables, there have been many studies of variables, such as relationships with the staff, the physical conditions, and other organizational issues in specific hospital units, with low levels of satisfaction associated with poor ratings of these variables.…”
Section: Introductionmentioning
confidence: 99%
“…AAs are more likely to perceive discrimination than other groups during the medical encounter (Halanych et al, 2011). Participatory physician visits are associated with higher patient satisfaction and better health outcomes for all groups (Clever, Jin, Levinson, & Meltzer, 2008).…”
Section: Discussionmentioning
confidence: 99%